Maximizing Network Lifetime of Directional Sensor Networks Considering Coverage Reliability - Joon-Min Gil; Jong Hyuk Park; Young-Sik Jeong (International Journal of Distributed Sensor Networks)
Directional sensor networks composed of a large number of directional sensors equipped with a limited battery and with a limited angle of sensing have recently attracted attention. Maximizing network lifetime is a challenge in developing energy-efficient directional sensor networks, while covering all of the targets in a given area. However, the existing schemes have considered target coverage problem as only the maximization of network lifetime. In real sensor networks, the quality of target coverage will be varied according to the detection probability of the sensors covering targets. In this paper, we address the directional cover-sets with coverage reliability (DCCR) problem of organizing directional sensors into a group of nondisjoint subsets to extend network lifetime maximally while maintaining networks' satisfied coverage reliability. For the DCCR problem, we first present a coverage reliability model that mainly takes into account the detection probability of each sensor in cover-sets and eventually supports coverage reliability for target coverage. We also develop a heuristic algorithm called directional coverage and reliability (DCR) greedy algorithm to solve the DCCR problem. To verify and evaluate the algorithm, we conduct simulations and show that it extends network lifetime to a reasonable degree while guaranteeing the minimum coverage reliability.